College of Health and Human Services names interim dean - Schock, Kathleen::::::::: (2013)
Fresno State appointed Dr. Jody Hironaka-Juteau as interim dean of the College of Health and Human Services. William A. Covino, provost and vice president for academic affairs, announced Hironaka-Juteau's selection on May 14.